Fluctuations in exchange rate and aggregate exports in Ukraine - Agiomirgianakis, George; Serenis, Dimitrios; Tsounis, Nicholas (Wahania kursów walut i ich wpływ na zagregowany eksport na Ukrainie, 2015)
This paper examines the effect of Exchange Rate Volatility (ERV) on the aggregate exports of Ukraine during the period of 1990 to 2013 using quarterly data. In the literature, it is found that exchange rate volatility causes a reduction in the overall level of trade. The paper tests this finding for Ukrainian foreign trade in the aforementioned period using the Autoregressive Distributed Lags (ARDL) method to co-integration. Overall, our findings suggest that there is a negative effect of ERV on Ukrainian exports. From a policy prospective, this result is important because it suggests that policy makers should consider the negative effect of ERV on exports when exercising exchange rate policy for balance of payment purposes
Ekonometria = Econometrics, 2015, Nr 4 (50), s. 11-23
Keywords: exchange rate volatility; exports; Ukraine; ARDL method; zmienność kursów walut; eksport; Ukraina; metoda ARDL